Analisis Keberlanjutan dan Keanekaragaman Hayati Taman Kehati Ciherang Sebagai Sarana Edukasi - Farhan Arianda; Septian Hadi Nugraha; Restu Pamuji (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
Biodiversity is an important indicator in assessing the condition of ecosystems and their sustainability. In addition, biodiversity conservation is an important manifestation of a company's commitment to the Sustainable Development Goals (SDGs) and environmental responsibility. This study aims to identify the biodiversity of flora and fauna and assess the sustainability level of the “Taman Kehati Ciherang” owned by PT Tirta Investama Plant Ciherang. This study used methods including direct inventory of flora and fauna, calculation of diversity indices using the ShannonWiener index, and sustainability analysis using a multiaspect sustainability analysis (MSA) approach. The results of the study found that the diversity index values obtained were 4.64 for flora and 4.37 for fauna, indicating a high diversity category. The overall sustainability score reached 73.33, which falls into the sustainable category, with the ecological, economic, and social aspects also falling into the same category. These biodiversity and sustainability values indicate that the Ciherang Nature Park of PT Tirta Investama Plant Ciherang serves as a biodiversity conservation area with sustainable potential and can be further developed as an implementation of the company's corporate social responsibility